KONSEP ORGANISASI & MANAJERIAL PENDIDIKAN VOKASI PADA PRODI REKAYASA KESELAMATAN KEBAKARAN - Rizki, Muhamad; Shinta Doriza; Agung Dudung (UNIVERSITAS BENGKULU, 2023)
This research was conducted with the aim of describing how the concepts and managerial systems in theFire Safety Engineering study program at the State University of Jakarta are. In this study, data collection used theinterview method with the Head of the Fire Safety Engineering Study Program itself, namely Mr. Catur SetyawanKusumohadi, M.T., Ph.D. The results of this study, the concept and managerial system in the Fire SafetyEngineering Study Program are said to have not run perfectly like other study programs at the State University ofJakarta. This is because the employees in the Fire Safety Engineering study program are all male and not female.Because some jobs have to be done by women, but because there are no female employees and the work has to bedone, men do the work. That's what causes the Fire Safety Engineering study program to have a C accreditation, dueto a shortage of female workers.